KAJIAN LITERATUR ANALISIS KEAMANAN JARINGAN - Pratikno, Raga Sakti; Trinata, Cakra; Hertantyo, Galuh Boy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Wireless network security is an important aspect in maintaining the operational continuity of an organization, especially with the increasing cyber threats to network infrastructure. This study aims to analyze the methods that have been used in securing Wireless Access Points (WAP) through the Systematic Literature Review (SLR) approach. The review process was carried out using the PRISMA method, which involves selecting literature based on certain inclusion criteria from various academic sources such as Google Scholar. From the selection results, 30 scientific journals were analyzed to identify the methods used in testing wireless network security. The research findings show that Penetration Testing is the most common method used in network security analysis. In addition, other techniques such as Deauthentication Attack, Port Scanning, Wardriving Attack, and Wireless Intrusion Detection System (WIDS) are also applied in various studies. The results of this review confirm that WAP security requires a comprehensive and sustainable testing strategy to anticipate evolving cyber threats.